Faktor-Faktor yang Mempengaruhi Kinerja Manajerial dalam Pengelolaan Keuangan Daerah dengan Kepuasan Kerja sebagai Variabel Intervening - Lisdana, Cakra Dwi; Supeno, Bambang (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to examine and analyze the effect of budgetary participation and budget transparency on job satisfaction as a connecting variable in carrying out managerial activities which include planning, investigation, coordination, evaluation, supervision, staffing, negotiation, and representation activities. The population in this study were all civil servants (PNS) within the Kampar Regency Regional Apparatus Organization. The sample selection used a purposive sampling method , amounting to 198 respondents. This type of research is quantitative research. This study uses the SmartPLS analysis tool with the SEM (Structural Equation Modeling) analysis method. Of the 198 questionnaires distributed, only 157 returned. The results of this study explain that budget participation does not have a direct effect on managerial performance, but budget participation does affect managerial performance through job satisfaction. while budget transparency influences directly or indirectly on managerial performance. Keywords: Budget Participation, Budget Transparency And Job Satisfaction, Managerial Performance